2023
DOI: 10.1002/etc.5745
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Changes in Trace Metal Bioavailability in the Sediment Pore water of a Constructed Wetland Using Passive Pore water Samplers

Zeinah Elhaj Baddar,
Xiaoyu Xu,
Breann Spencer

Abstract: Sediments in aquatic systems often act as a major sink for contaminants. Diffusive gradient in thin films (DGTs) and in situ equilibrium dialysis samplers (peepers) are two major in situ porewater sampling devices that overcome the problems associated with conventional porewater sampling methods. In this study, DGTs and peepers were used to study the spatial and seasonal effects (cool months: October‐February, warm months: May‐September) on metal bioavailability in the H‐02 constructed wetland, and the sink vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Compared to the cool months, which exhibited a population of 5.37 × 10 06 ± 25 g.cell –1 , the Desulfuromonas population was significantly ( p <0.0001) lower during the warm months (1.70 × 10 04 ± 2 g.cell –1 ) because sulfur oxidation is less likely as O 2 solubility decreases with increasing temperatures, implying less sulfur oxidation and more sulfur staying in reduced forms (Table S2). Qin et al, 2022, and Elhaj Baddar et al, 2023, recently reported that sulfate concentrations in the pore water of the H-02 constructed wetlands were significantly lower during the warm months. So, it is highly likely that the higher sulfate concentrations in the cool months were not due to increased SO 4 2– production, but rather to the lower rates of SO 4 2– removal by the smaller SRB population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the cool months, which exhibited a population of 5.37 × 10 06 ± 25 g.cell –1 , the Desulfuromonas population was significantly ( p <0.0001) lower during the warm months (1.70 × 10 04 ± 2 g.cell –1 ) because sulfur oxidation is less likely as O 2 solubility decreases with increasing temperatures, implying less sulfur oxidation and more sulfur staying in reduced forms (Table S2). Qin et al, 2022, and Elhaj Baddar et al, 2023, recently reported that sulfate concentrations in the pore water of the H-02 constructed wetlands were significantly lower during the warm months. So, it is highly likely that the higher sulfate concentrations in the cool months were not due to increased SO 4 2– production, but rather to the lower rates of SO 4 2– removal by the smaller SRB population.…”
Section: Resultsmentioning
confidence: 99%
“…This study constituted a comprehensive 10-month investigation spanning both the cooler period (from October 2021 to February 2022) and the warmer season (from May 2022 to September 2022), as extensively detailed in ref . In brief, passive water samplers were deployed once a month throughout the specified time frame mentioned above, with each deployment lasting 8 days.…”
Section: Methodsmentioning
confidence: 99%